Actividad lúdica y su incidencia en la lecto-escritura de los estudiantes del 3er año de educación básica de la Unidad Educativa Adolfo María Astudillo, Babahoyo 2023 - Bedon Naranjo, Olga Samanta (2023)
Reading and writing is an important skill in children's development and success in education and life in general. Because it allows early intervention of these crucial skills for optimal development in early childhood. Developing and achieving all types of skills in students. The objective of this research is to determine the incidence of recreational activities in the learning of reading and writing in the area of language and literature in 3rd year EGB students of the Educational Unit¨ Adolfo María Astudillo¨ of the Babahoyo 2023 canton. The methodology applied in the research conforms to the type of descriptive approach, since it focuses on describing and correlating the variables proposed, such as: Playful activities and their impact on reading and writing. This type of design has the main objective of providing a detailed description of the events, situations or phenomena under study, as well as identifying relationships between the variables without necessarily establishing causal relationships. The techniques applied were interviewing and observing teachers, including a series of questions that were answered as class hours passed. The results according to the findings found through the research process indicate that the playful strategies or games implemented are not appropriate and that teachers do not apply these strategies periodically since they can have a negative impact on the students' teaching-learning process.